INNOVATION OF POPULATION ADMINISTRATION SERVICES IN INTEGRATED ADMINISTRATIVE SERVICES (PATENT) IN MAKASSAR CITY - Sakawati, Herlina; Chairunnisa, Tarisca Amelia; Nur, Andi Cudai (Jurnal Aktor, 2024)
This study aims to innovate in population administration services in Integrated Administrative Services (PATEN) in Rappocini District, Makassar City, in this study using the theory of Rogers (1983) the characteristics of innovation, namely: a). Relative Advantage (relative suitability), b) Compatibility (suitability), c). Complexity, d). Trialibility, and e). Observability. This type of research is qualitative research with data collection techniques, namely observation, interviews, and documentation. The data obtained from the results of the research were processed using data reduction data analysis techniques, data presentation and conclusion drawn. The results of the study show that Innovation in Population Administration Services in Integrated Administrative Services (PATEN) in Rappocini District, Makassar City is already in the good category when viewed from several indicators, namely: Relative Advantage (relative suitability), Compatibility (suitability), Complexity (complexity), Trialibility (trial), and Observability (observability). However, it needs to be optimized on the Complexity indicator so that adopters are more aware of the extent to which this innovation will be used in the future.